Case Report: Exercise-induced normalization of chronic left bundle branch block: a rare recovery-phase phenomenon - Dor-haim, Horesh; Davarashvili, Ilia (Frontiers in Physiology, 2026)
BackgroundTransient left bundle branch block (LBBB) is associated with various cardiac and systemic conditions, including exercise-induced ischemia. However, normalization of baseline LBBB following exertion is a rare and poorly understood phenomenon.Case SummaryWe report the case of an 83-year-old male with longstanding coronary artery disease and baseline LBBB who underwent a routine stress echocardiogram. During the recovery phase, ECG monitoring revealed normalization of LBBB with first-degree AV block. Concurrent stress echocardiography showed improved segmental and global ventricular function.ConclusionThis case highlights a rare instance of post-exercise resolution of LBBB and suggests a possible link between exercise-induced autonomic modulation and transient improvement in conduction. Further research is warranted to explore the prognostic significance of this finding in patients with structural heart disease.